A quantitative analysis of the spatial and temporal evolution patterns of the bluetongue virus outbreak in the island of Lesvos, Greece, in 2014. Issue 5 (10th April 2020) - Malesios, Chrisovalantis; Chatzipanagiotou, Myrsini; Demiris, Nikolaos; Kantartzis, Apostolos; Chatzilazarou, Georgios; Chatzinikolaou, Stauroula; Kostoulas, Polychronis
Abstract: Bluetongue virus (BTV) causes an infectious disease called bluetongue, a vector‐borne viral disease of ruminants, which has major implications and causes severe economic damage due to its effect on livestock. These economic costs are mostly ascribed to the trade restrictions imposed during the epidemic period. In August 2014, an epidemic of bluetongue occurred in the island of Lesvos, Greece. The epidemic was severe and evolved over time, lasting until December 2014. The total cases of infected farms were 490, including a total number of 136, 368 small ruminants. In this paper, we describe a bluetongue virus serotype 4 (BTV‐4) epidemic and utilize Bayesian epidemic models to capture the spatio‐temporal spread of the disease. Our study provides important insights into the drivers of BTV transmission and has implications for designing control strategies. The results showed strong spatial autocorrelations, with BTV being more likely to spread between farms located nearby. The spatial modelling results proposed a certain spatial radius ( 12 km) around the onset of a similar epidemic for imposing restrictions on animal movement, which can be sufficient for the control of the disease and limit economic damage.